Method for preparing lithium-sulfur battery functional diaphragm material by taking LDH (layered double hydroxide) with metal cation defects of different valence states as lithium-sulfur battery functional diaphragm material

By loading LDH with different valence metal cation defects on the positive electrode side separator of the lithium sulfur battery, the problem of shuttle effect and slow redox kinetics in the lithium sulfur battery is solved, and the battery performance is significantly improved.

CN119725980AActive Publication Date: 2025-03-28DALIAN UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411879972.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

In practical applications, lithium-sulfur batteries face problems such as shuttle effect and slow redox kinetics, resulting in rapid attenuation of electrochemical performance and cycle life.

Method used

Multifunctional diaphragm materials such as NiFeAl-VIII-LDH/CNS and NiFeZn-VII-LDH/CNS are constructed by loading layered double hydroxides (LDH) with different valence states on the surface of the CNS of the conductive carbon substrate. These materials effectively adsorb and intercept polysulfides through the vacancy defects in their different coordination environments, reduce the energy barrier of the catalytic reaction and improve the catalytic conversion rate.

Benefits of technology

It effectively suppresses the shuttle effect in lithium-sulfur batteries, improves the cycle stability and rate performance of the battery, and significantly improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725980A_ABST
    Figure CN119725980A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a lithium-sulfur battery functional diaphragm material by taking LDH with different valence metal cation defects as a lithium-sulfur battery functional diaphragm material. CNS is selected as a conductive carbon substrate, and NFM (III) is prepared. And under the action of KOH, etching specified metal ions to respectively prepare NFM-VIII with divalent and trivalent cation defects, and finally preparing the lithium-sulfur battery diaphragm with the functionalized intermediate layer. According to the design, LDH with adjustable components is used as a catalytic substrate, cation vacancies derived from trivalent and divalent metals are successfully introduced into NiFe-LDH, then the microenvironment of O atoms near the cation vacancy defects is adjusted on the atomic scale, so that the binding capacity of unsaturated ligands O and Li exposed in LiPSs is optimized, the LiPSs are adsorbed and are catalyzed to be converted, and the NiFe-LDH / Li composite material is obtained. The shuttle inhibition effect is achieved, the catalytic conversion reaction process of LiPSs is promoted, and the electrochemical performance of the Li-S battery is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lithium-sulfur battery positive electrode side diaphragm materials and relates to a method for preparing LDH with metal cation defects in different valence states as a functionalized diaphragm material for a lithium-sulfur battery. Background Art

[0002] The growing demand for portable electronic devices, electric vehicles, and drones has greatly promoted the exploration of high-performance and low-cost energy storage devices.

[0003] Nowadays, with the booming development of new energy, more and more portable devices, vehicles and energy storage facilities are used in daily life. Traditional commercial lithium-ion batteries (LIBs) cannot meet the growing energy demand. Therefore, there is an urgent need to seek a new battery system with higher energy density. Among them, lithium-sulfur batteries (Li-S) have a high theoretical specific capacity (1675mAh g -1 ), and at the same time, the active substances of sulfur are widely distributed on the earth, which is conducive to large-scale production and application. In addition, it has low toxicity and is environmentally friendly, and is considered to be a powerful alternative to commercial lithium-ion batteries. Although they have excellent electrochemical properties, they still face many thorny problems in practical applications, including the "shuttle effect" of soluble polysulfides and the slow redox kinetics inside the battery, which can lead to rapid attenuation of electrochemical performance and cycle life. Therefore, how to inhibit the shuttle effect has become a top priority.

[0004] In recent years, people have made great efforts to develop and optimize targeted electrocatalysts for lithium-sulfur battery systems. The introduction of defects can not only increase the number of exposed active sites in the catalyst, but also effectively reduce the energy barrier of the catalytic reaction to sulfides, greatly improving the catalytic conversion rate of polysulfides. 2 In the article "with sulfur vacancy as a superior cathode for lithium-ion batteries", sulfur vacancies were introduced into VS 2Nanosheets, the increase of unsaturated sites and the optimized charge distribution synergistically lead to enhanced battery performance. In the article "Layered double Hydroxides-MXene heterointerfaces with abundant anionvacancies expediting sulfur redox kinetics for High-Performance Lithium–Sulfur batteries", Shen et al. enhanced the catalytic activity of LDH and MXene by introducing oxygen vacancies into LDH and anchoring them on MXene nanosheets. This approach produced a multifunctional synergistic effect and promoted the effective adsorption and conversion of polysulfides. However, most reported studies only focused on exploring the role of anion vacancies, and the exploration of the role of cation vacancies is still very insufficient. Among them, layered double hydroxide (LDH) materials have been widely studied due to their unique structure and adjustable composition. LDH, as a two-dimensional layered material composed of two or more metal elements, is composed of positively charged divalent and trivalent metal cations and interlayer anions. It has compositional diversity and structural tunability, and can effectively adsorb and catalyze the conversion of LiPSs. By utilizing the adjustable structure and composition of LDH, the electronic structure and chemical properties of the LDH surface can be further regulated by optimizing the types and proportions of divalent and trivalent metals, and LDHs with cation defects of different valences can be further constructed. The activity of LDHs can be enhanced by finely regulating their composition and structure, which alleviates the "shuttle effect" from a chemical perspective and accelerates the conversion of LiPSs. At the same time, these defect sites reduce the energy barrier of the catalytic reaction of sulfides and greatly improve the catalytic conversion rate of polysulfides. In addition, CNS, as the conductive carbon substrate of LDH, has a complex honeycomb structure, which is conducive to the transfer of lithium ions and electrons, which is of great significance for the practical application of lithium-sulfur batteries. Summary of the invention

[0005] In view of the above problems, the present invention proposes a method for preparing a functionalized diaphragm material on the positive electrode side for lithium-sulfur batteries, wherein LDH with different valence metal cation defects is loaded on the surface of CNS to construct a multifunctional diaphragm material, which is recorded as NiFe-LDH / CNS, NiFeAl-VIII-LDH / CNS, and NiFeZn-VII-LDH / CNS, wherein CNS, as a conductive carbon substrate, is conducive to the transfer of lithium ions and electrons, and provides LDH itself with relatively excellent conductivity, and the surface-loaded NiFeAl-VIII-LDH / CNS and NiFeZn-VII-LDH / CNS containing trivalent and divalent metal cation vacancy defects. Due to the vacancy defects with different coordination environments, polysulfides can be effectively adsorbed and trapped to prevent the shuttle effect of lithium-sulfur batteries. At the same time, these defect sites reduce the energy barrier of the catalytic reaction of sulfides, greatly improving the catalytic conversion rate of polysulfides.

[0006] The technical solution of the present invention:

[0007] A method for preparing LDH with different valence cation defects as a functionalized diaphragm material for a lithium-sulfur battery comprises the following steps:

[0008] (1) Preparation of CNS dispersion

[0009] Sodium citrate was carbonized in a tube furnace under the protection of a mixed atmosphere of hydrogen and argon with a volume ratio of 1:9. The carbonized product was placed in a hydrochloric acid solution at 20-30°C and stirred for 4-6 hours, then washed with deionized water until the solution pH was 6-7, and then dried at 60-80°C overnight to obtain the product CNS. CNS was ultrasonically dispersed in deionized water to obtain 0.5 mg ml -1 CNS dispersion;

[0010] (2) Preparation of NFM(III)

[0011] To Ni (NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O, CO(NH 2 ) 2 and NH 4 Adding a metal precursor M to F to obtain a mixture; adding the mixture to a CNS dispersion to fully dissolve to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction at 120° C. for 10-12 h and cooling to room temperature; washing the precipitate obtained by the hydrothermal reaction with deionized water and anhydrous ethanol three times, and drying it in vacuo at 60-80° C. to obtain NFM (III);

[0012] (3) Preparation of NFM-VIII

[0013] Immerse NFM (III) in a 1.5-2M KOH solution, then wash the product with water and ethanol until the pH is 6-7; after vacuum drying at 60-80° C. for 10-12 hours, obtain product A, which is NFM-VIII;

[0014] (4) Preparation of functionalized membrane

[0015] PVDF, conductive carbon black and product A are prepared into a slurry, stirred at 20-30°C for 10-12h, and then attached to a Celgard 2325PP diaphragm with a scraper. Finally, the slurry is vacuum dried in an oven at 60-80°C to obtain a positive electrode side functionalized diaphragm for a lithium-sulfur battery.

[0016] In step (1), the carbonization time is 1-2 hours, the carbonization temperature is 100-200°C, and the cooling rate from the carbonization temperature to room temperature is 1-10°C min -1 .

[0017] In step (1), the concentration of the hydrochloric acid solution is 4-5M.

[0018] In step (2), Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O, metal precursor M, CO(NH 2 ) 2 NH 4 The molar ratio of F is 6:1:1:40:20 to 12:1:1:40:20, among which Ni(NO 3 ) 2 6H 2 The concentration of O in the mixed solution is 0.003 M.

[0019] In step (2), the metal precursor M is a trivalent metal Al(NO 3 ) 3 9H 2 O、Cr(NO 3 ) 3 9H 2 O、Co(NO 3 ) 3 6H 2 O or divalent metal Zn(NO 3 ) 2 6H 2 O、Mg(NO 3 ) 2 6H 2O, Ca(NO 3 ) 2 6H 2 O.

[0020] In step (4), the mass ratio of PVDF, conductive carbon black and product A is 1:2:7.

[0021] In step (4), the scraped thickness is 100-200 μm.

[0022] Beneficial effects of the present invention:

[0023] The present invention obtains CNS by high-temperature carbonization and acidification of sodium citrate, then grows LDH on the surface of CNS by hydrothermal reaction, and finally alkali-etches the ternary LDH to obtain NiFeAl-VIII-LDH / CNS and NiFeZn-VII-LDH / CNS containing trivalent and divalent cation defects. The carbon substrate of the diaphragm has a complex honeycomb structure, which is conducive to the transfer of lithium ions and electrons, and is conducive to the adsorption of polysulfides. The NiFeAl-VIII-LDH / CNS and NiFeZn-VII-LDH / CNS containing trivalent and divalent metal cation vacancy defects loaded on the surface can effectively adsorb and intercept polysulfides due to vacancy defects with different coordination environments, and prevent the shuttle effect of lithium-sulfur batteries. At the same time, these defect sites reduce the catalytic reaction energy barrier to sulfides, greatly improving the catalytic conversion rate of polysulfides. The preparation method is simple, easy to obtain, low-cost, green and environmentally friendly, and suitable for industrial large-scale preparation and production.

[0024] The material is applied to lithium-sulfur batteries, effectively solving the serious shuttle effect and other problems in lithium-sulfur batteries, improving the battery cycle stability and rate performance, and showing excellent electrochemical performance. NiFeAl-VIII-LDH / CNS and NiFeZn-VII-LDH / CNS were used as the positive electrode separator of the battery. After 100 cycles at a current density of 0.5C, the specific capacities were 1041.7 mA h g -1 and 698.1mA hg -1 The capacity loss rate per cycle was 0.17% and 0.21%; when NiFe-LDH / CNS was used as the separator on the positive electrode side of the battery and cycled for 100 cycles at a current density of 0.5C, the specific capacity was only 425.3 mA h g -1 When the battery uses a blank PP separator, the specific capacity is only 327.5 mAh g after 100 cycles at a current density of 0.5 C. -1 . BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1This is a scanning electron microscope image of a positive electrode side separator for a lithium-sulfur battery prepared in Example 1 using NiFeAl-VIII-LDH / CNS containing trivalent defects.

[0026] Figure 2 This is a scanning electron microscope image of a positive electrode side separator for a lithium-sulfur battery prepared in Example 2 containing divalent defects NiFeZn-VII-LDH / CNS.

[0027] Figure 3 The graphs are the cycle performance diagrams of the lithium-sulfur batteries assembled in Examples 1 and 2 and Comparative Examples 1, 2 and 3, wherein (a) is the cycle performance diagram at a current density of 0.5C, and (b) is the cycle performance diagram at a current density of 1C.

[0028] Figure 4 This is a rate performance diagram of the lithium-sulfur batteries assembled in Examples 1, 2 and Comparative Examples 1, 2, and 3. DETAILED DESCRIPTION

[0029] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0030] Example 1

[0031] The preparation method of the NiFeAl-VIII-LDH / CNS composite material having trivalent metal cation defects after etching in this embodiment comprises the following steps:

[0032] (1) Preparation of CNS dispersion

[0033] Sodium citrate was heated at 5 °C min under the protection of a mixed atmosphere of hydrogen and argon with a volume ratio of 1:9. -1 The heating rate was increased from room temperature to 700 °C. After carbonization for 2 h, the product was placed in a 5 M hydrochloric acid solution at 25 °C and stirred for 4 h. It was then washed with deionized water until the solution pH was 6. After drying at 60 °C overnight, the product CNS was obtained. 30 mg CNS was ultrasonically dispersed in 60 ml deionized water to obtain 0.5 mg ml -1 CNS dispersion.

[0034] (2) Preparation of NFA

[0035] Will: Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O、Al(NO 3 ) 3 9H 2 O, CO(NH 2 ) 2 NH4 F was added to the CNS dispersion in a ratio of 6:1:1:40:20 and dissolved, wherein Ni(NO 3 ) 2 6H 2 The concentration of O was 0.003 M. The mixed solution was then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, hydrothermally heated at 120°C for 12 h and cooled to room temperature. Finally, the resulting precipitate was rinsed three times with deionized water and anhydrous ethanol, and vacuum dried in an oven at 60°C to obtain the desired product NFA.

[0036] (3) Preparation of NFA-VIII

[0037] The product NFA was soaked in a 2M KOH solution, and then the product was washed with water and ethanol until pH = 7; after vacuum drying at 60°C for 12 hours, NFA-VIII was obtained.

[0038] like Figure 1 As shown, it is a scanning electron micrograph of NFA-VIII, from which it can be observed that NFA-VIII is uniformly loaded on the CNS in a flower-like shape.

[0039] like Figure 3 As shown in the figure, after testing, the NFA-VIII prepared in Example 1 was used as a diaphragm modification material in a lithium-sulfur battery. After 100 cycles at a current density of 0.5C, the specific capacities were 1041.7 mA h g -1 The capacity attenuation rate is 0.17%, which has good cycle performance.

[0040] Example 2

[0041] The preparation method of the NiFeZn-VII-LDH / CNS composite material having divalent metal cation defects after etching in this embodiment comprises the following steps:

[0042] (1) Preparation of CNS dispersion

[0043] Sodium citrate was heated at 5 °C min under the protection of a mixed atmosphere of hydrogen and argon with a volume ratio of 1:9. -1 The heating rate was increased from room temperature to 700 °C. After carbonization for 2 h, the product was placed in a 5 M hydrochloric acid solution at 25 °C and stirred for 4 h. It was then washed with deionized water until the solution pH was 6. After drying at 60 °C overnight, the product CNS was obtained. 30 mg CNS was ultrasonically dispersed in 60 ml deionized water to obtain 0.5 mg ml -1 CNS dispersion.

[0044] (2) Preparation of NFZ

[0045] Will Ni(NO3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O、Zn(NO 3 ) 2 6H 2 O, CO(NH 2 ) 2 NH 4 F was added to the CNS dispersion in a ratio of 6:1:1:40:20 and dissolved, wherein Ni(NO 3 ) 2 6H 2 The concentration of O was 0.003 M. The mixed solution was then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, hydrothermally heated at 120 °C for 12 h and cooled to room temperature. Finally, the resulting precipitate was rinsed three times with deionized water and anhydrous ethanol, and vacuum dried in an oven at 80 °C to obtain the desired product NFZ.

[0046] (3) Preparation of NFZ-VII

[0047] The product NFZ was soaked in a 2M KOH solution, and then the product was washed with water and ethanol until the pH was 7; after vacuum drying at 80° C. for 12 h, NFZ-VIII was obtained.

[0048] like Figure 2 As shown, it is a scanning electron microscope image of NFZ-VII, and it can be observed that NFZ-VII is uniformly loaded on CNS in a flower shape.

[0049] like Figure 3 As shown in the figure, after testing, the NFZ-VII prepared in Example 1 was used as a diaphragm modification material in a lithium-sulfur battery. After 100 cycles at a current density of 0.5C, the specific capacities were 698.1 mA hg -1 The capacity decay rate is 0.21%, which has good cycle performance.

[0050] Example 3

[0051] The NiFeCr-VIII-LDH / CNS composite material with trivalent metal cation defects after etching in this embodiment is prepared by: on the basis of step (2) in embodiment 1, Al(NO 3 ) 3 9H 2 O is replaced by Cr(NO 3 ) 3 9H 2 O, and the rest remain unchanged.

[0052] Example 4

[0053] The NiFeCo-VIII-LDH / CNS composite material with trivalent metal cation defects after etching in this embodiment is prepared by: on the basis of step (2) in embodiment 1, Al(NO 3 ) 3 9H 2 O is replaced by Co(NO 3 ) 3 6H 2 O, and the rest remain unchanged.

[0054] Example 5

[0055] The NiFeMg-VII-LDH / CNS composite material with divalent metal cation defects after etching in this embodiment is prepared by: on the basis of step (2) in Example 2, Zn(NO 3 ) 2 6H 2 O is replaced by Mg(NO 3 ) 2 6H 2 O, and the rest remain unchanged.

[0056] Example 6

[0057] The NiFeCa-VII-LDH / CNS composite material with divalent metal cation defects after etching in this embodiment is prepared by: on the basis of step (2) in Example 2, Zn(NO 3 ) 2 6H 2 O is replaced by Ca(NO 3 ) 2 6H 2 O, and the rest remain unchanged.

[0058] Comparative Example 1

[0059] Only by adopting steps (1) and (2) of Example 1 and omitting step (3), an unetched NiFeAl-LDH / CNS composite material can be obtained.

[0060] Comparative Example 2

[0061] Only by adopting step (1) and step (2) of Example 2 and omitting step (3), an unetched NiFeZn-LDH / CNS composite material can be obtained.

[0062] Comparative Example 3

[0063] The preparation method of the NiFe-LDH / CNS composite material of this comparative example comprises the following steps:

[0064] (1) Preparation of CNS dispersion

[0065] Same as step (1) of Example 1.

[0066] (2) Preparation of NF

[0067] Will Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O, CO(NH 2 ) 2 NH 4 F was added to the CNS dispersion in a ratio of 6:1:40:20 and dissolved, wherein Ni(NO 3 ) 2 6H 2 The concentration of O was 0.003 M. The mixed solution was then transferred to a stainless steel autoclave lined with polytetrafluoroethylene, hydrothermally heated at 120 °C for 12 h and cooled to room temperature. Finally, the resulting precipitate was rinsed three times with deionized water and anhydrous ethanol, and vacuum dried in an oven at 80 °C to obtain the desired product NF.

[0068] Application Examples

[0069] The above-mentioned Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3, PVDF and conductive carbon black were dissolved in 700 μL N-methylpyrrolidone in a ratio of 7:1:2 to form a slurry. After stirring at 25°C for 12 hours, the slurry was scraped onto a Celgard 2325PP diaphragm with a scraper at a thickness of 200 μm. Finally, the slurry was vacuum dried in an oven at 60°C for 12 hours to obtain an LDH with cation defects of different valence states as a functional diaphragm for a lithium-sulfur battery.

[0070] (1) Preparation of lithium-sulfur batteries

[0071] Take 10 mg of polyvinylidene fluoride and dissolve it in 700 μL N-methylpyrrolidone, then add 90 mg of C / S composite material and stir to obtain C / S composite slurry. Take 14 μL of C / S composite slurry and apply it on one side of aluminum foil (12 mm diameter disc), vacuum dry it, and use it as the positive electrode of lithium-sulfur battery. The battery is assembled in a glove box, the lithium sheet is the negative electrode, and the Celgard 2325 separator scraped with NFA-VIII, NFZ-VII, NFA, NFZ, and NF materials is placed between the positive electrode and the lithium sheet. The electrolyte is a non-aqueous electrolyte containing 1M lithium bistrifluoromethanesulfonamide (LiTFSI) in 1,3-epoxypentane / ethylene glycol dimethyl ether (volume ratio 1:1), and 1% LiNO is added. 3 additives.

[0072] (2) Battery performance test of LDH with different valence cation defects as functionalized separator

[0073] After the battery was left to rest for 12 hours, the constant current charge-discharge cycle performance test and rate performance test were completed using the Blue Electric test system, with a test voltage window of 1.7–2.8 V. The current density of the rate performance test was 0.1C, 0.2C, 0.5C, 1.0C, 2.0C (1C = 1675 mA hg -1 The cyclic voltammetry curve was tested by electrochemical workstation with a scan rate of 0.05 mV s -1 . Figure 3 The cycle performance diagram of the lithium-sulfur battery and the comparative battery assembled with NFA-VIII and NFZ-VII separators in Example 1 at a current density of 0.5C. After 100 cycles at a current density of 0.5C, the specific capacities are 1041.7 mA h g -1 and 698.1mA hg -1 The capacity loss rate per cycle was 0.17% and 0.21%; when NF was used as the separator on the positive electrode side of the battery and cycled for 100 cycles at a current density of 0.5C, the specific capacity was only 425.3 mA hg -1 . Introducing metal cation defects of different valence states into LDH effectively improves its reaction kinetics. Among them, the unsaturated Ni-O-Fe coordination of trivalent metal cation defects is more effective in capturing and catalyzing LiPSs than the Ni-O-Ni coordination of divalent metal cation defects, forming Li-O covalent bonds with LiPSs, improving the chemical interaction between LDH and sulfur species, alleviating the shuttling effect of LiPSs, enhancing the nucleation affinity of liquid-solid phase transition, and realizing fast and durable sulfur electrochemistry. This study deepens the understanding of sulfur electrochemistry based on LDH, provides advanced structural design for high-performance lithium-sulfur batteries, and provides inspiration for rational material engineering in other energy storage and conversion fields.

[0074] (3) Scanning electron microscope (SEM) test: The modified lithium-sulfur battery separator material prepared in the embodiment was dried to prepare a sample, and then subjected to SEM test.

[0075] Finally, it should be noted that the above embodiment is only one of the specific implementations of the present invention. Although the description thereof is relatively detailed and specific, it cannot be understood as limiting the scope of the present invention. Those skilled in the art should understand that, within the scope of the present invention, equivalent replacements or modifications made to the present invention are within the technical solution content of the present invention and still fall within the protection scope of the present invention.

Claims

1. A method for preparing LDH with different valence cation defects as a functionalized diaphragm material for lithium-sulfur batteries, characterized in that: The following steps are involved: (1) Preparation of CNS dispersion Sodium citrate was carbonized in a tube furnace under the protection of a mixed atmosphere of hydrogen and argon with a volume ratio of 1:

9. The carbonized product was placed in a hydrochloric acid solution at 20-30°C and stirred for 4-6 hours, then washed with deionized water until the solution pH was 6-7, and then dried at 60-80°C overnight to obtain the product CNS. CNS was ultrasonically dispersed in deionized water to obtain 0.5 mg ml -1 CNS dispersion; (2) Preparation of NFM(III) Adding a metal precursor M to Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, CO(NH2)2 and NH4F to obtain a mixture; adding the mixture to a CNS dispersion to fully dissolve it to obtain a mixed solution; subjecting the mixed solution to a hydrothermal reaction at 120°C for 10-12h and cooling it to room temperature; washing a precipitate obtained by the hydrothermal reaction with deionized water and anhydrous ethanol three times, and drying it in a vacuum at 60-80°C to obtain NFM(III); (3) Preparation of NFM-VIII Immerse NFM (III) in a 1.5-2M KOH solution, then wash the product with water and ethanol until the pH is 6-7; after vacuum drying at 60-80° C. for 10-12 hours, obtain product A, which is NFM-VIII; (4) Preparation of functionalized membrane PVDF, conductive carbon black and product A are prepared into a slurry, stirred at 20-30°C for 10-12h, and then attached to a Celgard 2325PP diaphragm with a scraper. Finally, the slurry is vacuum dried in an oven at 60-80°C to obtain a positive electrode side functionalized diaphragm for a lithium-sulfur battery.

2. The preparation method according to claim 1, characterized in that: In step (1), the carbonization time is 1-2 hours, the carbonization temperature is 100-200°C, and the cooling rate from the carbonization temperature to room temperature is 1-10°C min -1 .

3. The preparation method according to claim 1, characterized in that: In step (1), the concentration of the hydrochloric acid solution is 4-5M.

4. The preparation method according to claim 1, characterized in that: In step (2), the molar ratio of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, metal precursor M, CO(NH2)2, and NH4F is 6:1:1:40:20 to 12:1:1:40:20, wherein: The concentration of Ni(NO3)2·6H2O in the mixed solution is 0.003M.

5. The preparation method according to claim 1, characterized in that: In step (2), the metal precursor M is a trivalent metal Al(NO3)3·9H2O, Cr(NO3)3·9H2O, Co(NO3)3·6H2O or a divalent metal Zn(NO3)2·6H2O, Mg(NO3)2·6H2O, Ca(NO3)2·6H2O.

6. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of PVDF, conductive carbon black and product A is 1:2:

7.

7. The preparation method according to claim 1, characterized in that: In step (4), the scraped thickness is 100-200 μm.

Citation Information

Patent Citations

  • Lithium-sulfur battery positive host material as well as preparation method and application thereof

    CN111463413A

  • Preparation method of diaphragm modification material for lithium-sulfur battery

    CN112886134A

  • Ni-N and Co-N loaded double active site doped hollow carbon sphere catalyst as well as preparation method and application thereof

    CN115020918A

  • Preparation method of Co0. 5Ni0. 5Te2 nanoparticle / three-dimensional carbon plate composite material and application of Co0. 5Ni0. 5Te2 nanoparticle / three-dimensional carbon plate composite material in lithium-sulfur battery

    CN118978146A

  • Layered double hydroxide film and composite material containing layered double hydroxide

    US20170260048A1